2018
DOI: 10.1002/jsfa.9030
|View full text |Cite
|
Sign up to set email alerts
|

Determination of changes in the concentration and distribution of elements within olive drupes (cv. Leccino) from Se biofortified plants, using laser ablation inductively coupled plasma mass spectrometry

Abstract: The biofortification of olive plants has allowed the enrichment of fruits with selenium. Enrichment with selenium has caused an increase in the concentration of other elements, which can change the nutritional quality of the drupes. The analytical technique used well as a valuable tool for routinely determining the chemical composition of all fruit parts. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
(64 reference statements)
0
6
1
Order By: Relevance
“…Lower concentrations of manganese were observed in Cornezuelo, Cornicabra and Picual varieties (1.4-1.8 µg g −1 , 1.9-3.0 µg g −1 and 1.16-1.40 µg g −1 , respectively) compared to those reported in bibliography in Leccino olives (7.8 µg g −1 ) [41]. On the other hand, the maximum phosphorus concentrations for the varieties under studied were 600 µg g −1 , 700 µg g −1 and 830 µg g −1 , respectively.…”
Section: Mineral Componentscontrasting
confidence: 59%
See 2 more Smart Citations
“…Lower concentrations of manganese were observed in Cornezuelo, Cornicabra and Picual varieties (1.4-1.8 µg g −1 , 1.9-3.0 µg g −1 and 1.16-1.40 µg g −1 , respectively) compared to those reported in bibliography in Leccino olives (7.8 µg g −1 ) [41]. On the other hand, the maximum phosphorus concentrations for the varieties under studied were 600 µg g −1 , 700 µg g −1 and 830 µg g −1 , respectively.…”
Section: Mineral Componentscontrasting
confidence: 59%
“…Overall, these concentrations are similar to that previously found in cv. Leccino [41] and higher than those in both Arbequina and Arauco cultivars [42].…”
Section: Mineral Componentsmentioning
confidence: 78%
See 1 more Smart Citation
“…Particularly, in olive trees ( Olea europaea L.), several beneficial effects of Se administered as sodium selenate via foliar spray at a concentration of 100–150 mg L −1 in pots and field experiments and of 10–30 mg L −1 added to the nutrient solution in hydroponics have been reported. Some of the reported effects are: improved drought and salt stress tolerance [ 14 , 15 , 16 ], increased oil phenol content [ 17 , 18 ], better pollen germination [ 19 , 20 ], and increased Se content in fruits [ 21 , 22 ]. However, no studies have been done on the possible beneficial effects of Se on olive tree in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, many studies have showed beneficial effects of selenium in processes such as immuno-endocrine, metabolic processes and in the maintenance of cellular homeostasis [4,5]. Moreover, the Se biofortification is considered as an agronomic-based strategy, utilized by farmers to produce Se-enriched food products which may help reduce dietary deficiencies in Se-deficient regions such as the Mediterranean Basin [6][7][8][9][10][11]. In recent years, the Se biofortification has shown beneficial effects in plants by increasing the antioxidant defense against reactive oxygen species (ROS) in vegetative growth and in the response to environmental stress [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%